Maternal healthcare services in a rural area of Haryana during the COVID-19 pandemic: A community-based study - Tejbeer Singh; Ravneet Kaur; Shashi Kant; Kalaivani Mani; Kapil Yadav; Sanjeev Kumar Gupta (Indian Journal of Community Medicine, 2023)
Background: It is well documented that the utilization of maternal healthcare services during pregnancy and childbirth plays a significant role in reducing maternal morbidity and mortality. Disruptions in maternal healthcare services during the coronavirus disease 2019 (COVID-19) pandemic have been reported. However, there is a paucity of literature from rural areas, as most of the previous studies are either record-based or conducted in tertiary care centers. This study aimed to determine the proportion of women who received the recommended maternal healthcare services during the COVID-19 pandemic and to study various factors associated with the utilization of services. Material and Methods: In this community-based study, we assessed the utilization of maternal healthcare services among 520 women residing in the Ballabgarh Block of District Faridabad, Haryana, whose antenatal, intrapartum, and postnatal period coincided with the first wave of COVID-19 pandemic. Domiciliary visits were made, and women were interviewed retrospectively regarding maternal healthcare services utilized by them. The antenatal care (ANC) cards were reviewed, and details were corroborated. Results: Full ANC was received by 15.3% of women, and 45% of women had less than four antenatal visits. 30.9% of participants had cesarean delivery. The proportion of cesarean delivery in private facilities was significantly higher than in government facilities [Odds Ratio (OR) (95% Confidence intervals (CI)) =10.04 (5.87–17.19); P < 0.001]. In multivariate logistic regression, gravidity was negatively associated with full ANC [OR (95% CI) =0.43 (0.25–0.74); P = 0.002]. Conclusion: Fewer women received the recommended maternal healthcare services during the COVID-19 pandemic. Detailed assessment of health systems and factors affecting routine healthcare services, during the pandemic, can help improve the readiness and response in the future.